If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7z + -1 = 2z + 19 Reorder the terms: -1 + 7z = 2z + 19 Reorder the terms: -1 + 7z = 19 + 2z Solving -1 + 7z = 19 + 2z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-2z' to each side of the equation. -1 + 7z + -2z = 19 + 2z + -2z Combine like terms: 7z + -2z = 5z -1 + 5z = 19 + 2z + -2z Combine like terms: 2z + -2z = 0 -1 + 5z = 19 + 0 -1 + 5z = 19 Add '1' to each side of the equation. -1 + 1 + 5z = 19 + 1 Combine like terms: -1 + 1 = 0 0 + 5z = 19 + 1 5z = 19 + 1 Combine like terms: 19 + 1 = 20 5z = 20 Divide each side by '5'. z = 4 Simplifying z = 4
| 10*x=8 | | 10x-6x-2x=10 | | 8z+12=5z-21 | | 2n-7n=45 | | 2(x-3)+2(x+4)=24 | | 17m=15 | | 2-21+1-35= | | 15m=14 | | 2x^4+10x^2+8=0 | | -2s=3s-0 | | 59-3x=15x+17 | | 8(-3x+1)=-23(x+1) | | 3.5y=14 | | 7-9x=139-37x | | (13b-7)-3(4b+1)=-6 | | 3x^4=-21 | | 6x-(5x+7)=-5 | | 6x+13=-67-10x | | 3x^4-21=0 | | 6x+5x+4+8=7x+4+3x | | 102-4x=4x+6 | | -6y+3=-7y+6 | | 18-n=10 | | 2-4x=17-7x | | 4p+7=13+3p | | 7+7+7+7+7+7+7+7-7-7-7-7-7-7-7-7-x+x= | | 7+7+7+7+7+7+7+7-7-7-7-7-7-7-7-7= | | 9+12x=42+x | | 2x^3+6x^2+18x+54=0 | | x^4+2x^3+3x^2+18x+54=0 | | 2x+2y=44 | | 2.6y+2=0.6y-6 |